Benefits and Challenges of Using NodeJS (International Journal of Innovative Research in Computer Science & Technology, 2022)
Node.js, the JavaScript runtime  environment is very popular among Full Stack Developers  for building Web applications. It gives the developer to  write server-side code in JavaScript and able to manage  both client and server side. Node.js ensures outstanding  performance, it applies event-driven, non-blocking input  output and asynchronous paradigm. The study is based on  benefits and challenges of using Node.js. The results of  study are from comparing different web development  programming languages with JavaScript which is used in  Node.js. And in the end some suggestions on how to  improve those areas and make it more feasible.
Keywords: Node.js; JavaScript; Asynchronous Function; Single-Thread; Front-end; Back end; Full-Stack